Additive manufacturing of polymer-derived ceramics: Materials, technologies, properties and potential applications. (July 2022) - Chaudhary, Raghvendra Pratap; Parameswaran, Chithra; Idrees, Muhammad; Rasaki, Abolaji Sefiu; Liu, Changyong; Chen, Zhangwei; Colombo, Paolo
Abstract: Artificially structured ceramic components with extraordinary properties are of immense demand in various industries. Additive manufacturing (AM) or 3D printing technologies are promising for the fabrication of ceramic components. However, printing of ceramics directly from their raw powders is a daunting task and requires multistep processing. Preceramic polymers (PCPs) offer an attractive pathway towards AM of preceramic structures featuring heterogeneous architectures and their direct conversion to polymer-derived ceramics (PDCs) – the corresponding ceramics. This review reports a detailed summary of recent research progress on the additive manufacturing of PCPs and the corresponding PDCs manufactured for different applications. The approaches towards the synthesis of various PCPs are discussed along with easily tunable chemical formulations that can be employed in AM processes. Further, the review discusses conventional PDC technology as well as AM technologies that can be employed with PCPs and the associated superiorities and drawbacks in comparison to powder-based ceramic 3D printing. Complex-shaped PDC structures and their properties and potential applications are also discussed. Overall, this review illustrates the AM capabilities of PCPs for cost-effective fabrication of advanced ceramics with high resolution, superior performance, lower environmental impact and new functionalities.